FOOD ADDITIVES IN COSMETICS – CLINICAL RELEVANCE - Viegas, Leonor Paulos (2014)
Food additives are substances added to foods that intentionally change their properties. They include antioxidants, coloring agents, emulsifiers, thickeners, flavoring agents and spices, preservatives and stabilizers. Their frequent use in food and cosmetic industries might be responsible for dermatosis in both food and food additives’ handlers and consumers, as well as in cosmetics users. Clinical presentations due to contact include contact urticaria and allergic or irritative contact dermatitis. The culprit allergen and dermatitis location differ depending on whether these occur in cosmetic users or in a professional context. Clinical presentations due to inhalation/ingestion of food additives might present as urticaria, anaphylaxis and systemic contact dermatitis. Diagnosis is based on a thorough clinical history and clinical exam, as well as cutaneous testing.